The optical manifestation of dispersive field‐aligned bursts in auroral breakup arcs. Issue 7 (22nd July 2013) - Dahlgren, H.; Semeter, J. L.; Marshall, R. A.; Zettergren, M.
Abstract : [1] High‐resolution optical observations of a substorm expansion show dynamic auroral rays with surges of luminosity traveling up the magnetic field lines. Observed in ground‐based imagers, this phenomenon has been termed auroral flames, whereas the rocket signatures of the corresponding energy dispersions are more commonly known as field‐aligned bursts. In this paper, observations of auroral flames obtained at 50 frames/s with a scientific‐grade Complementary Metal Oxide Semiconductor (CMOS) sensor (30° × 30° field of view, 30 m resolution at 120 km) are used to provide insight into the nature of the precipitating electrons similar to high‐resolution particle detectors. Thanks to the large field of view and high spatial resolution of this system, it is possible to obtain a first‐order estimate of the temporal evolution in altitude of the volume emission rate from a single sensor. The measured volume emission rates are compared with the sum of modeled eigenprofiles obtained for a finite set of electron beams with varying energy provided by the TRANSCAR auroral flux tube model. The energy dispersion signatures within each auroral ray can be analyzed in detail during a fraction of a second. The evolution of energy and flux of the precipitation shows precipitation spanning over a large range of energies, with the characteristic energy dropping from 2.1 keV to 0.87 keV over 0.2 s. Oscillations at 2.4 Hz in the magnetic zenith correspond to the period of the auroral flames, and the acceleration is believed to be due to Alfvenic wave interaction with electrons above the ionosphere. Key Points: Detailed optical measurements of auroral field‐aligned bursts of precipitation. Energy and flux evolution obtained continuously within individual auroral rays. Energy dispersion signatures in line with Alfven wave acceleration mechanism.